2015
DOI: 10.1159/000435819
|View full text |Cite
|
Sign up to set email alerts
|

Early Antidepressant Treatment and All-Cause 30-Day Mortality in Patients with Ischemic Stroke

Abstract: Background: Antidepressants, in particular selective serotonin reuptake inhibitors, have been associated with antithrombotic and neuroprotective properties and their more widespread use has been suggested in stroke recovery. However, data are sparse on their effects on the clinical outcome, including mortality, associated with early antidepressant treatment after stroke. We aimed to study all-cause 30-day mortality related to early antidepressant treatment in patients with ischemic stroke. Methods: We did a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
(30 reference statements)
2
13
0
Order By: Relevance
“…During the 6-month follow-up period, the cumulative incidence of antidepressant treatment or prescription was 35.2% (95% CI: 33.8-36.6) ( Figure 2). Among these, the majority As previously reported for this study population, 11 …”
Section: Re Sultssupporting
confidence: 56%
See 1 more Smart Citation
“…During the 6-month follow-up period, the cumulative incidence of antidepressant treatment or prescription was 35.2% (95% CI: 33.8-36.6) ( Figure 2). Among these, the majority As previously reported for this study population, 11 …”
Section: Re Sultssupporting
confidence: 56%
“…The defined study population has previously been included and described in detail in a study on outcome among patients treated with antidepressants during admission. 11 Please see Figure 1 for patient flow diagram.…”
Section: Study Populationmentioning
confidence: 99%
“…Further, there may be differences in genotype distributions in Korean versus Caucasian stroke patients and the EMOTION study included patients within 21 days, whereas our patients were included within 7 days. Consensus on the right timing of SSRI treatment post stroke is yet to be reached [18]; however, by including patients later, a possible beneficial effect of early SSRI treatment following stroke may be missed [19]. The mean age of the patients was lower in the EMOTION study, which may have led to an overall better pre-stroke cognitive status and less change in cognitive function, and thereby smaller differences between treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Significant associations within single studies were observed for thrombolysis (19), early medical assessment (24), OT assessment (17), and antidepressant therapy (20), but there 28 was no evidence for the association between stroke case fatality and hyperthermia management (28), and neurological assessment (35).…”
Section: [Insert Figure 2 Here]mentioning
confidence: 99%